Design, synthesis, and screening of novel ursolic acid derivatives as potential anti-cancer agents that target the HIF-1α pathway. Issue 6 (15th March 2019) - Wu, Jie; Zhang, Zhi-Hong; Zhang, Lin-Hao; Jin, Xue-Jun; Ma, Juan; Piao, Hu-Ri
Graphical abstract: Three novel series of ursolic acid derivatives containing an aminoguanidine moietiy were designed, synthesized, and evaluated for anti-tumor activity as HIF-1α inhibitors. Highlights: Three series of ursolic acid derivatives were designed and synthesized. The inhibitory effects on HIF-1α transcriptional activity and cytotoxicity of compounds were evaluated. Compound7b is a promising HIF-1α inhibitory hit as anticancer agent. The investigation of the mechanism on the mode of action of7b was performed. Abstract: The transcription factor hypoxia-inducible factor-1α (HIF-1α) plays an important role in tumor angiogenesis, growth, and metastasis and is recognized as an important potential therapeutic target for cancer. Here, we designed and synthesized three novel series of ursolic acid derivatives containing an aminoguanidine moiety and evaluated them as HIF-1α inhibitors and anti-cancer agents using human cancer cell lines. Most of the compounds exhibited significant inhibition of HIF-1α transcriptional activity, as measured using a Hep3B cell-based luciferase reporter assay. Among these compounds, 7b was the most potent inhibitor of HIF-1α expression under hypoxic conditions (IC50 4.0 µM) and did not display significant cytotoxicity against any cell lines tested. The mechanism of action of7b was investigated, we found that7b downregulated HIF-1α protein expression, possibly by suppressing its synthesis, reduced production of vascular endothelial growth factor, and inhibited the proliferation of cancer cells.